1) 3a-7b-6a+8b 2) 3,3a-2,8a-4+0,5a 3)10x-(3x+1)+(x-4) 4) 4(3c-4)+7 5) 2(2t-1) -7(t+10) 6) 7x-(5x-(3x+y)) 7) 1 2 2 - (a+6)- 7 - (3-a) 3 3 8) 0,6a+0,4(a-55) Упростите выражение пожалуйста.
1) 3a-7b-6a+8b
2) 3,3a-2,8a-4+0,5a
3)10x-(3x+1)+(x-4)
4) 4(3c-4)+7
5) 2(2t-1) -7(t+10)
6) 7x-(5x-(3x+y))
7) 1 2
2 - (a+6)- 7 - (3-a)
3 3
8) 0,6a+0,4(a-55)
Упростите выражение пожалуйста.
Ответ(ы) на вопрос:
1) 3a-7b-6a+8b=-3a+b
2) 3,3a-2,8a-4+0,5a=a-4
3)10x-(3x+1)+(x-4)=10x-3x-1+x-4=8x-5
4) 4(3c-4)+7=12c-16+7=12c-9
5) 2(2t-1) -7(t+10)=4t-2-7t-70=-3t-72
6) 7x-(5x-(3x+y))=7x-(5x-(3x+y))=7x-(5x-3x-y)=7x-5x+3x+y=5x+y
7) 2 - (a+6)- 7 - (3-a) = 2 - a-6- 7 - 3+a=-14 ( не совсем понятно написано)
8) 0,6a+0,4(a-55) =0,6a+0,4a-22=а-22
Не нашли ответ?
Похожие вопросы